Interchangeable usage of ‘organized-unorganized’ and ‘formal-informal’ classifications: An analysis through the social security lens - Roopali Shekhawat; Sandhya Kumari (Social Sciences and Humanities Open)
The interchangeable use of the terms ‘unorganized’ and ‘informal’ for both sectors as well as the workers, along with the common reference to the ‘organized-unorganized’ dichotomy in both these classifications complicate the labour policy formulation and implementation. Further, while the sectors are demarcated on several factors like incorporation status, employee size, use of capital, the organized and unorganized workers are differentiated on their sectoral engagement, with access to social security being the prime factor, without specifying the other terms and conditions of employment like paid leaves, and a written contract. Such ambiguities, on one hand, and oversimplifications, on the other, impede effective policy making and implementation, hindering workers' access to labour benefits, especially for the ones outside the ambit of the labour law framework.Hence, this paper hypothesizes that unambiguous definitions of the organized-unorganized sectors and the formal-informal workers would enhance labour law compliance and improve the access to benefits for a larger segment of workers in the unorganized sector. Against this backdrop, the researchers suggest specific parameters for classifying establishments into organized and unorganized sectors and the workers into formal and informal categories. This doctrinal research is based on the critical analysis of the international and national literature, especially government and non-government reports, case-laws, and legislations.